PENERAPAN SISTEM DRAFTINGPADA LAPORAN AUDIT DAN EXPOSURE DRAFT KUALITAS AUDIT - Marcella Evangelista Putri Kamasetya; Yulida Army Nurcahya (Universitas Prof.Hazairin,SH Bengkulu, 2020)
Along with the times, humans are required to have superior potential and ability so that they can face competition and development in all aspects. In addition, we must also be able to adjust to policies that have been established with good ethics. One of them can be through practical work activities in which students are involved to be directly involved in the world of work and apply the knowledge gained in the relevant institutions. One of them is a way or a drafting system that is good and right in accordance with predetermined standards with the aim of facilitating the reader in reading and understanding the contents and intentions of auditors in the audit report, in which the auditor must be thorough, careful, ethical, and have competence when working on design. Not only that, the auditor must also have and implement a general application of the code of ethics that has been issued by IAPI in the Public Accountant Professional Code of Ethics. This code of ethics includes, the introduction and basic principles of professional ethics, integrity, objectivity, prudence and professional competence, confidentiality, professional behavior.